2011
DOI: 10.1002/gps.2498
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol use disorders identification test (AUDIT) and its derivatives in screening for heavy drinking among the elderly

Abstract: The AUDIT and AUDIT-C are accurate in screening for heavy drinking among the elderly if the cut points are tailored to this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 16 publications
1
70
2
5
Order By: Relevance
“…The US National Institute on Alcohol Abuse and Alcoholism recommends that healthy adults aged over 65 years who do not take medications should not drink more than 3 drinks (42 g alcohol) per day or 7 drinks (92 g alcohol) per week [6]. Yet 10.8% of men and 2.9% of women in a large US sample aged over 65 reported exceeding these limits, compared with 28.6% of men and 10.3% of women in a UK sample the same age [7] and just over a fifth of samples of comparable age in Finland and Belgium [8]. In the USA, 23% of men and 9% of women aged 50–64, and 14% of men and 3% of women aged 65 and above, report binge drinking (consuming five or more drinks) on at least one occasion in the preceding month [9], while 27% of Europeans aged over 54 years report doing so on a weekly basis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The US National Institute on Alcohol Abuse and Alcoholism recommends that healthy adults aged over 65 years who do not take medications should not drink more than 3 drinks (42 g alcohol) per day or 7 drinks (92 g alcohol) per week [6]. Yet 10.8% of men and 2.9% of women in a large US sample aged over 65 reported exceeding these limits, compared with 28.6% of men and 10.3% of women in a UK sample the same age [7] and just over a fifth of samples of comparable age in Finland and Belgium [8]. In the USA, 23% of men and 9% of women aged 50–64, and 14% of men and 3% of women aged 65 and above, report binge drinking (consuming five or more drinks) on at least one occasion in the preceding month [9], while 27% of Europeans aged over 54 years report doing so on a weekly basis [10].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested the use of AUDIT-5, a brief version of AUDIT consisting of items 2, 4, 5, 9 and 10. By using a sub-group of the Finnish population aged 65–74, Aalto et al, [12] suggested a cut-off score of five instead of eight. This result is not necessarily valid for people aged above 74 year but their main conclusion was that AUDIT is still valid for higher ages but at lower cut-offs.…”
Section: Introductionmentioning
confidence: 99%
“…The other variations were always less prevalent among those aged 75 years compared to younger ones aged 65e74 years 12 , results that support another study 16 . However, in a study conducted in Finland among 804 elderly individuals aged 65e74 years, high consumption of alcohol was found in 22.8% of the sample 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Various tools can be used to identify the abusive consumption of alcohol among elderly patients 16 , and the Alcohol Use Disorder Identification Test (AUDIT), which is a questionnaire with 10 items specifically related to alcohol, developed by WHO 17 , has been widely used in population samples, including elderly people, showing appropriate sensitivity to diagnose alcohol abuse among the elderly 16,18 .…”
Section: Introductionmentioning
confidence: 99%